Vector Autoregressive Modeling on Cases of Malaria Based on the Tribal in Tanah Bumbu District - Khair, Abdul; Sarmanu, Sarmanu; Martini, Santi; Otok, Bambang Widjanarko (CAUCHY, 2018)
The number of malaria in this area always has the tendency of the most compared to the city/district in South Kalimantan Province. Behavior is internalisation factor from the level of knowledge, attitudes and actions of a person who influenced by customs, customs and belief in certain things that has been handed down by his ancestors. The behavior of a community group can be different from the other groups so that they formed a group behavior or can be said tribal behavior.The purpose of this research predicts that the number of the prevalence of malaria in Tanah Bumbu tribal based with Y1t : the tribe of Banjar, Y2t : Javanese,  Y3t : the tribe of Bugis, and Y4t : other tribes using vector autoregressive (VAR) model. The results of the study showed with Granger Causality approach there is a relationship between the amount of the prevalence of Malaria Javanese with other tribes, Bugis tribe with other tribes. The relationship is strengthened in the VAR model, which is the number of the prevalence of Malaria Javanese influenced by the number of the prevalence of Malaria Javanese at period t-1, and the number of the prevalence of Malaria tribe Bugis at period t-1. While the number of the prevalence of Malaria tribe Bugis influenced by the number of the prevalence of Malaria Other tribes in the period t-2.